Associations between FTO genotype and total energy and macronutrient intake in adults: a systematic review and meta‐analysis. Issue 8 (28th May 2015) - Livingstone, K. M.; Celis‐Morales, C.; Lara, J.; Ashor, A. W.; Lovegrove, J. A.; Martinez, J. A.; Saris, W. H.; Gibney, M.; Manios, Y.; Traczyk, I.; Drevon, C. A.; Daniel, H.; et al.
Summary Risk variants of fat mass and obesity‐associated (FTO) gene have been associated with increased obesity. However, the evidence for associations between FTO genotype and macronutrient intake has not been reviewed systematically. Our aim was to evaluate the potential associations between FTO genotype and intakes of total energy, fat, carbohydrate and protein. We undertook a systematic literature search in OVID MEDLINE, Scopus, EMBASE and Cochrane of associations between macronutrient intake and FTO genotype in adults. Beta coefficients and confidence intervals (CIs) were used for per allele comparisons. Random‐effect models assessed the pooled effect sizes. We identified 56 eligible studies reporting on 213, 173 adults. For each copy of the FTO risk allele, individuals reported 6.46 kcal day−1 (95% CI: 10.76, 2.16) lower total energy intake (P = 0.003). Total fat (P = 0.028) and protein (P = 0.006), but not carbohydrate intakes, were higher in those carrying the FTO risk allele. After adjustment for body weight, total energy intakes remained significantly lower in individuals with the FTO risk genotype (P = 0.028). The FTO risk allele is associated with a lower reported total energy intake and with altered patterns of macronutrient intake. Although significant, these differences are small and further research is needed to determine whether the associations are independent of dietary misreporting.